Familial hemophagocytic lymphohistiocytosis in a neonate: Case report and literature review. Issue 47 (24th November 2021) - Yang, Yue; Luo, Zebin; Yuan, Tianming
Abstract: Rationale: Familial hemophagocytic lymphohistiocytosis (FHL) is a potentially fatal disease that rarely presents in the neonatal period. Timely diagnosis is a key challenge owing to the atypical clinical manifestations. Here, we describe a case of FHL type 3 with disease onset in the early neonatal period and review the relevant literature. Our findings may provide insights into the diagnosis and treatment of this rare disease. Patient concerns: A 6-day-old male neonate presented with fever, hepatosplenomegaly, cytopenia, hyperferritinemia, hypofibrinogenemia, hemophagocytosis, and hypertriglyceridemia. Diagnosis: Considering the clinical picture (prolonged fever, progressive hepatosplenomegaly, high triglycerides, low fibrinogen, and high ferritin), along with abnormal natural killer-cell activity, combining sequence analysis of genomic DNA results (compound heterozygous mutations of UNC13D ), the patient was finally diagnosed with FHL type 3 (FHL3). Interventions: The patient was initially treated with HLH-1994 protocol and subsequently switched to an oral regimen of ruxolitinib due to incomplete remission of the disease. Outcomes: The trend of change in weekly cytokine levels, neutrophil counts, hemoglobin, and platelet counts indicated that the complete remission was not achieved after the treatment of HLH-1994 protocol. The platelet counts fluctuated within the normal range after oral administration of ruxolitinib. But soon after, the patient did not respond to treatment and eventually died of respiratory failure. Lesson: Timely diagnosis of FHL is challenging. This case report illustrates that thrombocytopenia can be the first clinical sign of FHL with neonatal onset. Genetic testing, detection of cytokines, and flow cytometry should be performed as soon as possible to confirm the diagnosis. Given the high morbidity and mortality of FHL, pediatricians should have a high suspicion index for this disease.